LO094: Mass casualty incident training for rural Canadian municipalities: a mobile education unit initiative. (2nd June 2016) - Besserer, F.; Hogan, M.; Oliver, T.; Froh, J.
Abstract : Introduction / Innovation Concept: The Shock Trauma Air Rescue Society (STARS®) is a charitable, non-profit organization that is dedicated to providing a safe, rapid, highly specialized emergency medical transport system for the critically ill and injured. The STARS® Mobile Education Unit (MEU) is comprised of a high fidelity simulation suite that mimics a hospital emergency room, installed in a specially equipped motorhome (SEM) that can wirelessly operate a high fidelity human mannequin. The MEU provides an excellent opportunity to combine continuing medical education for resuscitation and MCI management. At present, no formal MCI education process exists in Saskatchewan.Curriculum, Tool, or Material: The Saskatchewan STARS® MEU delivers a phased MCI education initiative to rural and regional centers within the province. The educational initiative is sub-divided into three stages: 1. pre-exercise knowledge translation using a flipped classroom approach, 2. on-site tabletop exercise (TTX) and, 3. high-fidelity simulation session with a review of MCI management principles . Sites perform a Hazard Vulnerability Analysis (HVA) following stage 2 and the highest identified site-specific risks are utilized during the development of the simulated scenarios for stage 3. During stage 2, participants also complete a pre and post-exercise survey. The survey evaluates the educational component, the tabletop exercise component and the perceived pre and post tabletop exercise competencies for the management of MCI. In the pilot project, two regional sites completed the tabletop exercise. The pre-exercise survey evaluated perceived MCI and disaster preparedness for the region. Only 8% and 25% of participants at each site respectively, reported that their disaster plan had been trialed in tabletop, full exercise or real activation within the past three years. Participants strongly agreed that the tabletop exercise was a valuable experience (86% and 88% respectively). More robust data will become available as the initiative transitions out of the pilot stage to formal operations.Conclusion: A formal MCI training program implemented through the STARS® MEU for rural Saskatchewan municipalities enables participants and their organizations to both review and enhance their current emergency management plans. This initiative will aim to establish a foundation for future collaboration at the provincial and national level for rural MCI training and preparedness.